2023
DOI: 10.3390/cryst13060890
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Na(I) Coordination Complex with s-Triazine Pincer Ligand: Synthesis, X-ray Structure, Hirshfeld Analysis, and Antimicrobial Activity

Amal Yousri,
Ayman El-Faham,
Matti Haukka
et al.

Abstract: The pincer ligand 2,4-bis(3,5-dimethyl-1H-pyrazol-1-yl)-6-methoxy-1,3,5-triazine (bpmt) was used to synthesize the novel [Na(bpmt)2][AuCl4] complex through the self-assembly method. In this complex, the Na(I) ion is hexa-coordinated with two tridentate N-pincer ligands (bpmt). The two bpmt ligand units are meridionally coordinated to Na(I) via one short Na-N(s-triazine) and two slightly longer Na-N(pyrazole) bonds, resulting in a distorted octahedral geometry around the Na(I) ion. In the coordinated bpmt ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Over the past ten years, there has been a lot of interest in the self-assembly of supramolecular structures involving metal coordination compounds because of their potential uses in many domains such as catalysis [1][2][3] and biological systems [4]. In coordination chemistry, multi-dentate ligands play a significant role because they can form metal complexes with extra stability as a result of the chelate effect [5][6][7][8][9][10][11]. First row transition metals have a variety of coordination numbers and can be used to bind ligands to create coordination complexes with diverse of coordination geometries [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past ten years, there has been a lot of interest in the self-assembly of supramolecular structures involving metal coordination compounds because of their potential uses in many domains such as catalysis [1][2][3] and biological systems [4]. In coordination chemistry, multi-dentate ligands play a significant role because they can form metal complexes with extra stability as a result of the chelate effect [5][6][7][8][9][10][11]. First row transition metals have a variety of coordination numbers and can be used to bind ligands to create coordination complexes with diverse of coordination geometries [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the application of metal complexes in medicine, especially in cancer therapy [16][17][18], bacterial infection treatment [19,20], and as antifungal agents [21,22], has attracted widespread interest. In particular, metal complexes of sulfadiazine have drawn much attention by many researchers [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Drugs with 1,2,4-triazine moiety were found in many synthetic and natural products, such as lamotrigine and azaribine, which have significant pharmacological effects [29]. Also, there are several examples of biologically active complexes with triazine ligands [30][31][32][33][34]. Previous studies [35,36] showed that the addition of planar-condensed aromatic ligands containing nitrogen (whose donor characteristics are similar to those of pyrimidine and purine bases) to anti-tumor agents leads to intriguing features that can be used to create new drugs.…”
Section: Introductionmentioning
confidence: 99%